Study of some Morphological Characters in Coconut (Cocos nucifera L.) as Effected by Organic and Inorganic Fertilizers Amendments in Sandy Loam Soil of Karachi, Pakistan - Solangi, Abdul Hameed; Iqbal, M. Z.; Baloch, Parwiaz Ahmed (CORD, 2017)
A comparison is made on the effect of organic and inorganic fertilizers on the some morphological characters of coconut. The study demonstrated that the treatments T1 Nitrogen, Phosphorus and Muriate of potash (NPK) + Neem seed powder (NSP) + Gliricidiasepium leaves (GSL) and T2 (NPK+ GSL) significantly increased most of the morphological characters (stem girth, number of leaves, petiole and leaflets). The study revealed that vegetatively the coconut was grown well on soil amended with organic and inorganic fertilizers. The morphological characters i.e the stem girth (173.77 cm) of coconut at 20 cm height T1 (NPK + NSP + GSL) treatment produced maximum girth as compared to T2 to T8 T2 (NPK+ NSP), T3 (NPK+ GSL), T4 (NSP + GSL), T5 (NPK), T6 (GSL), T7 (NSP), T8 (Control) treatments. The 11 leaf scars length (80.44 cm) was significantly (p<0.05) highest in T1 as compared to T3 to T8 treatments. The present study also revealed that the number of leaves (28.77) were significantly (p<0.05) greater in T1 as compared to T5 to T8 treatments. The petiole length (139.44 cm) and thickness (3.27 cm), were found significantly (p<0.05) highest in T1 as compared to T8 treatment. Leaflets length and number of leaflets were significantly high in T1 and T2 as compared to T3 to T8 treatments while, the leaflets width (5.04 cm) was significantly high in T1 as compared to other treatments. It is therefore, recommended that treatment T1 NPK (1.0:0.5:1.0kg) + NSP (10.0kg) + GSL (20.0kg)/palm/year was enough to improve the morphological characters to enhance future productivity.